2009
DOI: 10.1007/s00455-009-9207-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oropharyngeal Air-Pulse Stimulation on Swallowing in Healthy Older Adults

Abstract: While previous research has shown that air-pulse stimulation of the oropharynx facilitates saliva swallowing in young adults, the effects of air pulses in older adults have not been examined. Responses to air-pulse stimulation may differ in young and older adults given age-related changes in sensation, swallowing physiology, and swallow-related brain activation. Therefore, this study sought to determine the effects of oropharyngeal air-pulse stimulation on saliva swallowing rates in 18 healthy older adults. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The absence of a significant correlation between the onset-screening interval and the SPM value suggests that spontaneous swallowing frequency is a robust indicator of dysphagia at different time points during the acute phase of stroke. Also, age is reported to contribute to reduction in spontaneous swallowing frequency [29, 39, 40] . However, in this cohort of acute stroke patients age did not correlate significantly with swallow frequency rate.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a significant correlation between the onset-screening interval and the SPM value suggests that spontaneous swallowing frequency is a robust indicator of dysphagia at different time points during the acute phase of stroke. Also, age is reported to contribute to reduction in spontaneous swallowing frequency [29, 39, 40] . However, in this cohort of acute stroke patients age did not correlate significantly with swallow frequency rate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with air puffs during flexible endoscopy also suggest that the pharyngeal sensation changes with age [107, 108, 112]. The use of air puff stimulation as a mechanism to elicit swallowing is currently under investigation [113, 114]. These studies suggest that healthy individuals experience a strong urge to swallow in response to air puffs directed at the posterior faucial arches.…”
Section: Potential Mechanisms To Alter Swallowingmentioning
confidence: 99%
“…Theurer, et al 106,107 (2005, 2009) evaluated the effects of air-pulse stimulation on swallowing outcomes in healthy adults. The researchers found that air puff-pulse stimulation to the oropharynx resulted in an 'irrepressible urge-to-swallow' as reported by the participants 106 .…”
Section: Urge-to-actmentioning
confidence: 99%
“…The researchers found that air puff-pulse stimulation to the oropharynx resulted in an 'irrepressible urge-to-swallow' as reported by the participants 106 . This resulted in an increased swallowing frequency 106,107 . More recently, our laboratory studied the pharyngeal swallowing of people with PD and dysphagia under dual task conditions.…”
Section: Urge-to-actmentioning
confidence: 99%